Global change and investments in smallholder irrigation for food and nutrition security in Sub-Saharan Africa - Hanjra, Munir A.; Williams, Timothy O. (Springer, 2020)
Investments in irrigation contribute to poverty reduction and enhance food security. This paper considers irrigation investments more broadly in the context of rural–urban linkages and thus examines rural irrigation schemes and peri-urban and urban agriculture using freshwater, groundwater and wastewater. We present case studies from East, West and Southern Africa, while focusing on the imperative of smallholders and of food security and nutrition. Evidence from Big Data and telecoupling show that, amid global change and sustainability issues, irrigation development strengthens connections between humans and nature with notable benefits to food security. Transforming investments to feed the future generation require priority investments in irrigation, solar energy for groundwater pumping, groundwater development policy, and integration of peri-urban and urban agriculture into food systems. Equally important will be no-regret interventions in wastewater reuse, water storage and groundwater buffer, micro-irrigation, and wholesale reconfiguration of farming systems, through anticipatory investments, to safeguard food security and sustainability into the distant future.